Ultrasound triggered release of Trastuzumab-conjugated immunoliposomes targeting breast cancer - Ahmed, Amal Elsadig Elamir (2018)
A Master of Science thesis in Chemical Engineering by Amal Elsadig Elamir Ahmed entitled, “Ultrasound triggered release of Trastuzumab-conjugated immunoliposomes targeting breast cancer”, submitted in December 2018. Thesis advisor is Dr. Ghaleb Husseini and thesis co-advisor is Dr. Rana Sabouni. Soft and hard copy available.